Probing functional self-assembled molecular architectures with solution/solid scanning tunnelling microscopy. Issue 75 (6th August 2018) - Cui, Daling; MacLeod, Jennifer M.; Rosei, Federico
Abstract : STM is emerging as a tool to elucidate and guide the use of self-assembled molecular systems in practical applications, including small molecule device engineering, molecular recognition and sensing and electronic modification of 2D materials. Abstract : Over the past two decades, solution/solid STM has made clear contributions to our fundamental understanding of the thermodynamic and kinetic processes that occur in molecular self-assembly at surfaces. As the field matures, we provide an overview of how solution/solid STM is emerging as a tool to elucidate and guide the use of self-assembled molecular systems in practical applications, focusing on small molecule device engineering, molecular recognition and sensing and electronic modification of 2D materials.